Kecenderungan ‘Aisyah R.A dalam Istinbȃth Hadis-Hadis Ahkȃm - Sri Wihidayati; Yusefri Yusefri (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
The Tendency of ‘Aisyah  R.A  in the Istinbȃth of Ahkȃm HadithsAisyah binti Abu Bakar r.a., was not only known as the wife of the Prophet PBUH, but also recognized as an intelligent female companion who narrated many hadiths and issued legal fatwas. Her fatwas were not infrequently different from other companions of the Prophet. The focus of this research object was the hadiths of ahkâm contained in several fatwas of Aisyah r.a. The purpose of this research was to reveal the tendency of the istinbâth of Aisyah r.a in analyzing the ahkâm hadiths. This research was qualitative descriptive, using the analytical methods of istinbâth theory and fiqh al-hadîs. The conclusion of this research extended to: first, that Aisyah not only witnessed many of the Prophet's traditions, but also tended to be critical and rational in understanding them. Second, between critical and rational attitudes could be seen in the use of semantic analysis of the meaning of a lafazh, historical and contextual, in the sense of social situations and conditions underlying the emergence of a hadith of the Prophet, or changes in social conditions that occurred at that time. Therefore, the tendency to the istinbâth of Aisyah was more likely to be bil al-ra'yi